2020
DOI: 10.1038/s41467-019-13911-x
|View full text |Cite
|
Sign up to set email alerts
|

Gut stem cell aging is driven by mTORC1 via a p38 MAPK-p53 pathway

Abstract: Nutrients are absorbed solely by the intestinal villi. Aging of this organ causes malabsorption and associated illnesses, yet its aging mechanisms remain unclear. Here, we show that aging-caused intestinal villus structural and functional decline is regulated by mTORC1, a sensor of nutrients and growth factors, which is highly activated in intestinal stem and progenitor cells in geriatric mice. These aging phenotypes are recapitulated in intestinal stem cell-specific Tsc1 knockout mice. Mechanistically, mTORC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 56 publications
(67 reference statements)
4
79
0
Order By: Relevance
“…SHH pathway inhibition significantly reduced mTORC1 activity in parallel with autophagy activation. Among the upstream signals of mTOR (p-AKT, p-AMPK α , p-ERK, and p-p38) 63 65 , p-AKT Ser473 likely mediates SHH-autophagy regulation, which was also supported by AM2 mouse data.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…SHH pathway inhibition significantly reduced mTORC1 activity in parallel with autophagy activation. Among the upstream signals of mTOR (p-AKT, p-AMPK α , p-ERK, and p-p38) 63 65 , p-AKT Ser473 likely mediates SHH-autophagy regulation, which was also supported by AM2 mouse data.…”
Section: Discussionmentioning
confidence: 56%
“…Experimental control groups included unstained, PE-stained, 7-AAD-stained, and positive dead cells. The cells were detected by a BD LSRFortessa TM flow cytometer and analyzed by FlowJo X software (Becton, Dickinson & Company, San Jose, CA, USA) 65 .…”
Section: Methodsmentioning
confidence: 99%
“…In the intestinal epithelium, the features of ageing are accompanied by cell cycle changes, oxidative stress and enhanced apoptosis [86]. Ageing of ISCs is driven by mTORC1 [87] as well as decreased activity of the Wnt signalling pathway [88]. In the gut, ageing impairing the balance between stem cell reserve and differentiation [80,89].…”
Section: Paneth Cells Affect Intestinal Stem Cells In Ageingmentioning
confidence: 99%
“…Nutrient malabsorption is common among the elderly and often causes illness [ 149 ]. He and coworkers [ 150 ] showed that aging-induced intestinal villus structural and functional decline is regulated by mammalian target of rapamycin complex 1 (mTORC1), which is a sensor of nutrients and growth factors that is highly activated in ISC and progenitor cells in geriatric mice. Their findings revealed that mTORC1 drives aging by augmenting a prominent stress response pathway in ISCs and identified p38 mitogen-activated protein kinase as an anti-aging target downstream of mTORC1 [ 150 ].…”
Section: Future Directionsmentioning
confidence: 99%